Ultrasonic-mediated production of carboxylated cellulose nanospheres. Issue 5 (October 2021) - Ayouch, Ikrame; Barrak, Ilias; Kassem, Ihsane; Kassab, Zineb; Draoui, Khalid; El Achaby, Mounir
Abstract: In this study, carboxy-functionalized spherical cellulose nanoparticles have been produced from Alfa plant-derived cellulose microfibers (CMF) using ultrasonic-induced cellulose fragmentation process. CMF, with fiber diameter of 7.26 µm and crystallinity of 87%, were firstly produced from Alfa plant fibers and then subjected to surface carboxylation using TEMPO-mediated oxidation process. The as-resulted TEMPO-oxidized CMF (T-CMF), with an average diameter of 2.72 µm, a crystallinity of 89% and carboxyl groups content of 1032 mmol COO - /Kg cellulose, were then exposed to ultrasonication treatment for 45 min, resulting in the formation of cellulose nanospheres (CNS) with an average diameter of 33.96 ± 7.01 nm and a crystallinity of 76%. The carboxyl groups content on the surface of CNS was measured at 945 mmol COO - /Kg cellulose. This study demonstrated the importance of the ultrasonication process as a green method for producing CNS with interesting properties, which can be used in various potential functional applications. Graphical Abstract: ga1 Highlights: TEMPO-oxidized cellulose microfibers have prepared from Alfa plant fibers. Carboxylic cellulose nanospheres were produced from oxidized cellulose by ultrasonic process. Cellulose nanospheres show an average sphere diameter of 34 nm and a crystallinity of 76%. Ultrasonication process is a green approach to produce sphere-like shape nanocellulose.